Modelling of dew point operating conditions in a rotary regenerative air heater - Brandt Warren (EDP Sciences, 2021)
Dew point related fouling of regenerative rotary air heaters contributes to efficiency reduction of coal-fired boilers. This fouling commonly causes high pressure differences over the air heater steel matrix, along with elevated leakage rates, resulting in increased loading of draught group fans. These increases also conduce to excessive erosion rates, introducing premature failure of element packs and draught group components. The research problem aimed to develop, and validate, a modelling tool to predict the onset of dew point related fouling for regenerative rotary air heaters (VBA RAH model). A modelling tool equip system engineers with the knowledge to enhance operating conditions and maintenance strategies, to prevent the onset of dew point related fouling. The results yielded that the cold end of the air heater packs experience sulphuric acid dew point related fouling for at 670MW(90% MCR), at 544MW(80% MCR) and at 468MW(68% MCR) of the exposure time to the flue gas stream. Different operating and design change configurations were simulated to find potential solutions to minimize dew point related fouling and improving boiler efficiency. The tool provides a platform for identifying methods to reduce maintenance costs and production losses, which will contribute to improved and sustainable operating of coal fired power generation plants.